Intranasal recombinant protein subunit vaccine targeting TLR3 induces respiratory tract IgA and CD8 T cell responses and protects against respiratory virus infectionResearch in context - Katharina Wørzner; Signe Tandrup Schmidt; Julie Zimmermann; Ahmad Tami; Charlotta Polacek; Carlota Fernandez-Antunez; Katrine Top Hartmann; Rune Fledelius Jensen; Julia Sid Hansen; Kristin Illigen; Louise Krag Isling; Gitte Erbs; et al. (EBioMedicine)
Summary: Background: Intranasal vaccines against respiratory viruses are desired due to ease of administration and potential to protect against virus infection of the upper respiratory tract. Methods: We tested a cationic liposomal adjuvant delivering the TLR3 agonist Poly (I:C) (CAF®09b) for intranasal administration, by formulating this with SARS-CoV-2 spike trimeric protein and assessing airway mucosal immune responses in mice. The vaccine was further evaluated in SARS-CoV-2 virus challenge models, using mice expressing the human ACE2 receptor and Syrian hamsters. Findings: The intranasal vaccine elicited both serum neutralising antibody responses and IgA responses in the upper respiratory tract. Uniquely, it also elicited high-magnitude CD4 and CD8 T cell responses in the lung parenchyma and nasal-associated lymphoid tissue. In contrast, parenteral administration of the same vaccine, or the mRNA-1273 (Spikevax®) vaccine, led to systemic antibody responses and vaccine-induced CD4 T cells were mainly found in circulation. The intranasal vaccine protected against homologous SARS-CoV-2 (Wuhan-Hu-1) challenge in K18-hACE2 mice, preventing weight loss and virus infection in the upper and lower airways. In Syrian hamsters, the vaccine prevented weight loss and significantly reduced virus load after challenge with the homologous strain and Omicron BA.5. Interpretation: This study demonstrates that intranasal subunit vaccines containing TLR3-stimulating cationic liposomes effectively induce airway IgA and T cell responses, which could be utilised in future viral pandemics. Funding: This work was primarily supported by the European Union Horizon 2020 research and innovation program under grant agreement no. 101003653.